(f + g)(9) = ?
A. 118
B. 112
C. 119
D. 114
E. 116
F. 111
G. 110
H. 115
I. 113
J. 117
Answer:
D
Step-by-step explanation:
Find (f + g)(x) then evaluate (f + g)(9)
(f + g)(x) = f(x) + g(x)
= 4x - 1 + x² - 2 = x² + 4x - 3
Now substitute x = 9 into the expression
(f + g)(9) = 9² + 4(9) - 3 = 81 + 36 - 3 = 114 → D
Answer:
J.117
Step-by-step explanation:
f(x) =4x-1
if f(2)= 4(2)-1
f(2)= 8-1 = 7
f(2) = 7 equation 1
g(x) =x2-2
if g(4)= (4)2-2
g(4) = 8-2 = 6 equation 2
Now,
(f+g)(9) =?
subtitute equation 1 and 2
(7+6)(9)=?
(13)(9)=?
13×9= 117
Hence, the answer is 117
B.1
C.5/9
D.-5/9